Geographical Distribution and New Host Associations of Rhyssomatus Subtilis (Coleoptera: Curculionidae) in Argentina - Cazado, Lucas Emiliano (2013)
The genus Rhyssomatus Schoenherr, 1837 includes 176 Neotropical and Nearctic species, many of which have agricultural importance because they are phytophagous during the larval and adult stages (O’Brien & Wibmer 1982; Wibmer & O’Brien 1986; Costa et al. 1988; Socías et. al. 2009)